(untitled) (Jurnal Geomine, 2015)
Asphalt is a thick liquid which is ahydrocarbonwith a poorsulfur, oxygen, andchlorine. This study aimed of to influencing differences in levels and analyze the factors that cause the differences in levels of drilling results with the stockpile. The research method that used is quantitative descriptive. As for the reguired data extraction samples obtained from the analysis of drilling results and stockpile. Of the research conducted, the levels asphalt from drilling result is26.18% greater than theasphalt content from stockpile resultsthatbitumen25.61%. the difference between the result of drilling asphalt assay with the stockpile is 0.57% bitumen. The unknown factors affecting differences in levels and the factors that cause the differences between the result of drilling asphalt assay with the stockpile is not evenly spread of assay, impurities on the asphalt, sampling, water and bitumen, as well as sample preparation.